Combination of medical and health care based on digital smartphone‐powered photochemical dongle for renal function management. Issue 9 (10th June 2019) - Fu, Yusheng; Tan, Haiyan; Wu, Xiujian; Wu, Xiaohe; Yang, Yongzheng; Gao, Yanling; Liu, Ruowei; Qi, Min; Chen, Xiaoyun; Ning, Yaochao; Sun, Weidong; Chang, Nianhuan; et al.
Abstract: Currently, the global healthcare market is increasing at high speed with the impendent global aging issue. Healthcare Industry 4.0 has emerged as an efficient solution towards the aging issue since it was integrated with ubiquitous medical sensors, big health processing platform, high bandwidth, speed technologies, and medical services, etc. It is believed to fulfil the requirement of the tremendously growing health market. The acquisition of medical data acts as the dominant precondition to implement the Healthcare Industry 4.0. In the same way, the widely available smartphone could serve as the best biomedical information collect station. In this study, a smartphone‐powered photochemical dongle is demonstrated to precisely estimate blood creatinine from the fingertip blood, which works as a highly compact reflectance spectral analyzer with an enzymatically dry chemical test strip. Comparing with conventional laboratory facility for the evaluation and treatment of chronic kidney disease (CKD), it implemented the platform of point care with agreed accuracy. In order to estimate the efficiency of treatment and recovery of the CKD, the proposed photochemical dongle would provide a flexible and rapid platform for point of care. Furthermore, the proposed measured technology is very promising method for remote CKD management.